On truth - Frankfurt, Harry G. 1929-2023 (Borzoi book, 2019)
A philosophical treatise on the nature of truth offers a common-sense and witty approach that examines what it is and its value in a world and culture that seems devoted to falsehood, lies, half-truths, and marketing jargon.